Coordinating heart morphogenesis: A novel role for Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels during cardiogenesis in Xenopus laevis. Issue 3 (4th May 2017) - Pitcairn, Emily; Harris, Hannah; Epiney, Justine; Pai, Vaibhav P.; Lemire, Joan M.; Ye, Bin; Shi, Nian-Qing; Levin, Michael; McLaughlin, Kelly A.
ABSTRACT: Hyperpolarization-activated cyclic-nucleotide gated channel (HCN) proteins are important regulators of both neuronal and cardiac excitability. Among the 4 HCN isoforms, HCN4 is known as a pacemaker channel, because it helps control the periodicity of contractions in vertebrate hearts. Although the physiological role of HCN4 channel has been studied in adult mammalian hearts, an earlier role during embryogenesis has not been clearly established. Here, we probe the embryonic roles of HCN4 channels, providing the first characterization of the expression profile of any of the HCN isoforms during Xenopus laevis development and investigate the consequences of altering HCN4 function on embryonic pattern formation. We demonstrate that both overexpression of HCN4 and injection of dominant-negative HCN4 mRNA during early embryogenesis results in improper expression of key patterning genes and severely malformed hearts. Our results suggest that HCN4 serves to coordinate morphogenetic control factors that provide positional information during heart morphogenesis in Xenopus .